Manajemen Zakat di BAZ Kabupaten Lumajang - Abdul Komar (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2015)
How are the efforts of BAZ and LAZ to get the obligatedzakat to give out their money, is something that need creation and innovation of policy management, moreover in order to be best-practices policy. Consequently, a policy which is considered best-practices need to be taken, analyzed, and evaluated, which then to be a benchmarking. Nowadays, searching of best-practices policy of an institution is a must, including in a zakat management. BAZ of Lumajang region has been showing the highest fund graphic in East Java for a few years, however this region does not have constitutional instrument in a form of PERDA Zakat. Furthermore, Lumajang region is not a unique demography for Islamic atmosphere of East Java compare to other regions. From this illustration, there must be best-practices policy in BAZ of Lumajang region, so it can be expected that there is zakat management benchmarking from BAZ of Lumajang region